Consumer-driven prepared food consumption policies: a sustainability perspective on reducing food waste - Bo Hou; Ying Chen; Zhiwei Wang (Frontiers in Sustainable Food Systems)
IntroductionFood waste is a global issue intricately linked to food crises and ecological degradation. The development of the prepared food industry and markets is a promising practice to reduce food waste globally and achieve carbon neutrality.MethodsThis study is grounded in the motivation -opportunity -ability (MOA) theory and employs a structural equation model (SEM) to establish an analytical framework to explore factors influencing the intentions of Chinese consumers to consume prepared food.ResultsEmpirical analysis reveals that motivation, opportunity, and ability positively influence consumers’ intentions to consume prepared food. Furthermore, opportunity and ability exert a mediating effect on motivation through convenience and health factors.DiscussionThis study innovatively applies the MOA theory to food waste issues, providing a new policy perspective. The conceptual framework developed offers a theoretical foundation for future research on pathways to reduce food waste, especially within the context of prepared food consumption in China, and serves as a theoretical starting point for academia, industry, and policymakers.